Glycopenic endometrium in infertility - Shivappa, Prateek; Isaacs, Roma; Mandrelle, Kavita; Goyal, Sunita (International Journal of Research in Medical Sciences, 2022)
Background: Infertility is a global health problem affecting 8-10% couples worldwide. Endometrium is considered to be sensitive indicator of ovarian, pituitary and hypothalamic function. The endometrium, which fails to produce adequate amount of glycogen is termed as ‘glycopenic uteri’. Glycopenic endometrium is said to be unfavourable for early blastocyst implantation leading to infertility in spite of ovulation. Endometrial aspiration/biopsy can be histologically dated based on the Dallenbach-Hellweg criteria which forms an essential part of histopathological examination of endometrium for infertility work-up. The aim of the study was to study the correlation of glycogen content with endometrial histomorphology in infertility. Methods: Cross-sectional observational study in which one hundred twenty-two endometrial specimens sent as curetting/ biopsy were studied. The Glycogen content of endometrium was graded from + to ++++ as given by Arzac and Blanchet. Statistical analysis was done on SPSS version 26.0. The categorical variables were represented by count (percentage) and the continuous variables were represented by mean±SD. The Chi-square test was used to find the association of glycogen content with infertility, the various phases of the endometrium and age. Results: Glycopenic endometrium was seen in 36.9% cases of infertility. Out of which, glycopenic endometrium was much more prevalent in patients with secondary infertility (47%) as compared to patients with primary infertility (35.1%). Conclusions: Glycogen depletion in secretory phase results in inadequate preparation of endometrium at the time of implantation. Assessment of glycogen is considered to be an essential part of histopathological examination.